(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
Contemporary Christianity has many faces, which mostly stand for different worship styles and available services. The present study focuses on the Polish and Italian religious entrepreneurs who operate as brands, and their modus operandi is based on the power evangelism approach introduced by John Wimber in the 1980s. The branding in question has been patterned on the corporate culture and driven by continuous allusions to the figure of Jesus Christ. The main objective of this study is to explore how power evangelism-oriented entrepreneurs cultivate consumer attachment to the brands they represent. The research also aims to identify the best-selling products and services and to investigate how particular suppliers compete for adherents. The investigation has been carried out using participant observation and the analysis of the audio-visual materials. An in-depth examination of the abovementioned phenomenon shows that the current religious marketplace has been filled with a great variety of tailored religious products made by skilled religious suppliers and offered on a regular basis to ever more challenging religious customers, mainly to attract them for longer and finally, to make them convert into declared brand loyalists.